2014
DOI: 10.1016/j.jmoldx.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

False Positives in Multiplex PCR-Based Next-Generation Sequencing Have Unique Signatures

Abstract: Next-generation sequencing shows great promise by allowing rapid mutational analysis of multiple genes in human cancers. Recently, we implemented the multiplex PCR-based Ion AmpliSeq Cancer Hotspot Panel (>200 amplicons in 50 genes) to evaluate EGFR, KRAS, and BRAF in lung and colorectal adenocarcinomas. In 10% of samples, automated analysis identified a novel G873R substitution mutation in EGFR. By examining reads individually, we found this mutation in >5% of reads in 50 of 291 samples and also found similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 19 publications
4
43
0
Order By: Relevance
“…All samples were analysed by targeted next generation sequencing of a custom panel of pancreatic driver genes using Ion AmpliSeq library preparation on an Ion Torrent Personal Genome Machine, and whole exome sequencing was performed on three selected cases by Personal Genome Diagnostics (Baltimore, Maryland, USA) 26. Mutations were identified using NextGENe software followed by visual inspection to minimise risk of artifactual calls 27. The relatedness of the lesions from each patient was determined by a categorical algorithm as described in the ‘Results’ section.…”
Section: Methodsmentioning
confidence: 99%
“…All samples were analysed by targeted next generation sequencing of a custom panel of pancreatic driver genes using Ion AmpliSeq library preparation on an Ion Torrent Personal Genome Machine, and whole exome sequencing was performed on three selected cases by Personal Genome Diagnostics (Baltimore, Maryland, USA) 26. Mutations were identified using NextGENe software followed by visual inspection to minimise risk of artifactual calls 27. The relatedness of the lesions from each patient was determined by a categorical algorithm as described in the ‘Results’ section.…”
Section: Methodsmentioning
confidence: 99%
“…A number of targeted NGS panels have been developed as research technologies, laboratory developed tests, and commercially available products and custom panels for assessing multiple types of clinical specimens 3,5,[10][11][12][13][14][15] . Reports from multiple studies have demonstrated the value of NGS as a sensitive and specific clinical tool for the detection of genomic alterations 3,[10][11][12]14 . Yet studies have also demonstrated the risk of artifacts which can cause false-positive results from challenging cancer biopsies such as FFPE specimens [2][3][4][5]12,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Reports from multiple studies have demonstrated the value of NGS as a sensitive and specific clinical tool for the detection of genomic alterations 3,[10][11][12]14 . Yet studies have also demonstrated the risk of artifacts which can cause false-positive results from challenging cancer biopsies such as FFPE specimens [2][3][4][5]12,14 . Additionally, recent publications have highlighted high failure rates for NGS using oncology specimens 16 and false-positive calls with commercial targeted NGS panels that are aggravated by the use of low-input DNA 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations